Estetyczne, eleganckie, piękne komunikaty. Wokół, adresowanej do mnie, korespondencji Profesor Ewy Rzetelskiej-Feleszko = Aesthetic, elegant, beautiful messages. Around the correspondence of professor Ewa Rzetelska-Feleszko addressed to me - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present unique in terms of content and form letters and postcards written to the author of the article by one of the most outstanding Polish scholars, who for the rest of her life was interested in science, the world and people.
Keywords: korespondencja; komunikacja językowa; estetyka; piękno; elegancja; correspondence; language communication; aesthetics; elegance; beauty